Effect of different drying methods on the degradation of selected flavonoids in Centella asiatica - Mohd Zainol, Mohamad Khairi; Abdul Hamid, Azizah; Abu Bakar, Fatimah; Pak Dek, Mohd Sabri (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
The effect of different drying methods on the degradation of flavonoids in Centella asiatica was evaluated. C. asiatica leaf, root and petiole were dried using air-oven, vacuum oven and freeze drier. Flavonoid was determined utilizing reverse-phase high performance liquid chromatography (RP-HPLC). Results of the study revealed the presence of high concentration of flavonoids in C. asiatica leaf, root and petiole, which include, naringin (4688.8 ± 69 μg/100 g, 3561.3 ± 205 μg/ 100 g, and 978.3 ± 96 μg/ 100 g), rutin (905.6 ± 123 μg/ 100 g, 756.07 ± 95 μg/ 100 g, and 557.25 ± 58 μg/ 100 g), quercetin (3501.1 ± 107 μg/ 100 g, 1086.31 ± 90 μg/ 100 g, and 947.63 ± 83 μg/ 100 g) and catechin (915.87 ± 6.01 μg/ 100 g, 400.6 ± 67 μg/ 100 g, and 250.56 ± 18 μg/ 100g). Luteolin, kaempferol and apigenin on the other hand, were inconsistently present in some parts of C. asiatica. Air-oven treatment resulted in the highest total flavonoids degradation followed by vacuum oven and freeze dried with percent degradation of 97%, 87.6% and 73%, respectively. Catechin and rutin were found to be the most stable flavonoids with percent degradation up to 35%, 66% and 76% for freeze dried, vacuum oven and air oven, respectively.